Concepts for the data flow control on the XIDer readout ASIC - Schimansky, David; Busca, P.; Collonge, M.; Fajardo, P.; Fischer, Paulina; Ritzert, Michael; Williams, M. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2023)
XIDer is a 2D pixelated hybrid X-ray detector that is supposed to act as a multi-purpose platform for diffraction experiments at fourth-generation high-energy synchrotron light sources like the Extremely Brilliant Source of the European Synchrotron Radiation Facility (ESRF-EBS). As such it needs to tackle a wide variety of requirements. These include x-ray energies of 30keV to 100keV imposing the utilisation of high-Z sensors, a wide dynamic range from single photons to fluxes of 1 × 109photonspixel−1s−1 and expected raw data rates up to the order of TBs−1 in the final detector design. As a result, XIDer’s readout ASIC has to provide smart and flexible ways for on-chip data pre-processing to reduce the output data rate to manageable sizes. This article focusses on introducing the ASIC’s novel and unique data-handling concepts like the custom-designed telegram protocol followed by the presentation of exemplary configurations and use cases.